MAIN STAGES IN THE DEVELOPMENT OF KEMEROVO BRANCH OF THE UNION OF WRITERS OF THE RUSSIAN SOVIET FEDERATIVE SOCIALIST REPUBLIC (1962 – THE 1980S) - A. M. Sherin (Вестник Кемеровского государственного университета, 2014)
The paper is devoted to formation and development of Kemerovo branch of the Union of Writers of the Russian Soviet Federative Socialist Republic, which was created in 1962. The research aims at identifying the stages in the development of Kemerovo literary organization and their main features. As a result, three main stages of development of the local branch of the Union of Writers were defined: the stage of formation (1962 – first half of the 1970s), the crisis stage (the second half of the 1970s) and the stage of sustainable development (the 1980s). In first stage, members of writers' organization had to perform tasks and solve problems of the Union. The main problem was irregular publications of the almanac «Ogni Kuzbassa». Many problems were solved in the first half of the 1970s, but since the middle of the 1970s writers of Kemerovo region encountered the crisis. The organization lost nearly a third of its members and had to send its efforts to attracting talented young writers. Staff crisis ended by the beginning of the 1980s. Writers' organization reached a new level of work with young authors in the 1980s, when literary studio «Pritomie» was created. Kemerovo branch of the Union of Writers reached a new level of development in the 1980s.